USE OF VIRTUAL ENVIRONMENTS IN TEACHING STUDENTS TO PROGRAM - Mirsanov , Uralboy Muhammadiyevich; Ravshanova , Gulhayo Azamatovna (Educational Research in Universal Sciences, 2024)
Thisin the article programming of languagesopportunities, studentsto programming from virtual environments in teachingto use about offer and recommendation given.